2017
DOI: 10.1007/s00109-017-1575-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of foam cell formation in atherosclerosis

Abstract: Low-density lipoprotein (LDL) and cholesterol homeostasis in the peripheral blood is maintained by specialized cells, such as macrophages. Macrophages express a variety of scavenger receptors (SR) that interact with lipoproteins, including SR-A1, CD36, and lectin-like oxLDL receptor-1 (LOX-1). These cells also have several cholesterol transporters, including ATP-binding cassette transporter ABCA1, ABCG1, and SR-BI, that are involved in reverse cholesterol transport. Lipids internalized by phagocytosis are tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
399
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(406 citation statements)
references
References 153 publications
2
399
1
4
Order By: Relevance
“…Once adherent to the vascular surface, monocytes enter the intima and differentiate into macrophages that take up modified LDL to form foam cells. 34 A recent study elegantly demonstrated that senescent foam cells with reduced telomere length are vital for plaque buildup, and in later stages, plaque remodeling and rupture. 35 These senescent cells show heightened profiles of proatherogenic and proteolytic factors, including IL-1α, TNFα, MMP-3, MMP12, MMP13, MCP-1, and VCAM-1.…”
Section: Atheroscleros Ismentioning
confidence: 99%
“…Once adherent to the vascular surface, monocytes enter the intima and differentiate into macrophages that take up modified LDL to form foam cells. 34 A recent study elegantly demonstrated that senescent foam cells with reduced telomere length are vital for plaque buildup, and in later stages, plaque remodeling and rupture. 35 These senescent cells show heightened profiles of proatherogenic and proteolytic factors, including IL-1α, TNFα, MMP-3, MMP12, MMP13, MCP-1, and VCAM-1.…”
Section: Atheroscleros Ismentioning
confidence: 99%
“…Atherosclerosis and its complications rank as the leading cause of cardiovascular mortality with the hallmarks of lipid deposition and inflammatory response. The oxidative modification of sequestered lipoproteins triggers the migration of circulating monocytes into the subendothelial space and differentiation into macrophages, which rapidly engulf modified LDL and transform into foam-cell formation (1)(2)(3). Macrophages that accumulate in atherosclerotic plaques seem to have a diminished capacity to migrate.…”
mentioning
confidence: 99%
“…VSMCs are a source of foam cells, which are the defining pathologic characteristic of atherosclerotic plaques (22). Intracellular lipid homeostasis reflects a balance of cholesterol uptake, endogenous synthesis, and cholesterol export.…”
Section: Discussionmentioning
confidence: 99%